Challenging Identification of a Novel PiISF and the Rare PiMmaltonZ α1-Antitrypsin Deficiency Variants in Two Patients. Issue 5 (1st May 2014) - Suh-Lailam, Brenda B.; Procter, Melinda; Krautscheid, Patti; Haas, Jason; Kumar, Shiva; Mao, Rong; Grenache, David G.
Abstract: Objectives: α1 -Antitrypsin (AAT) deficiency is associated with an increased risk for lung and liver disease. Identification of AAT deficiency as the underlying cause of these diseases is important in correct patient management. Methods: AAT deficiency is commonly diagnosed by demonstrating low concentrations of AAT followed by genotype and/or phenotype testing. However, this algorithm may miss novel AAT phenotypes. Results: We report two cases of AAT deficiency in two patients: a case of the novel phenotype PiISF, misclassified as PiII by phenotyping, and a case of the rare phenotype PiMmalton Z misclassified as PiM2 Z. Conclusions: These cases highlight the importance of understanding the limitations of a commonly used diagnostic algorithm, use of further gene sequencing in applicable cases, and the potential for underdiagnosis of AAT deficiency in patients with chronic obstructive pulmonary disease.